(untitled) (Research, Society and Development, 2021)
Objective: To report the experience of educational actions carried out with teachers, students, residents of the municipality and professionals who work in primary care in relation to the prevention of breast cancer in the city of Divinópolis-MG. Methods: This is a descriptive study, an experience report, based on educational health activities in relation to breast cancer, in the city of Divinópolis - MG. Held with teachers, students, health professionals and residents of the municipality of Divinópolis / MG, during the years 2017 and 2018. Results: Approximately 6,000 people benefited from the educational activities, which were carried out during the months of June to December of the years from 2017 and 2018. During this period, educational activities were carried out at Basic Health Units (UBS) and at the State University of Minas Gerais / Divinópolis. Conclusion: The educational actions on breast cancer made it possible to live meaningful and enriching experiences for the personal, academic, and professional aspects.